(Study of the Impact of Goats on the production of Goat Meat in Sudan compared to the Arab Countries in the period (2015- 2008 - El- Kanany, Mohamed Mahmoud (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to demonstrate the impact of goats on the production of goat meat in Sudan compared to the Arab countries in the period (2015- 2008). The study used the descriptive method to identify goats and produce goat meat in Sudan, and the historical approach to follow the development in the preparation and production of the statistical curriculum and the Excel program for analyzing data and information. Data and information were collected from official secondary sources, especially reports, books, and articles. The study concluded for a range of results, that Sudan achieved the largest number of goats in comparison to the Arab countries in the period (2008- 2012) reached 38260. 20 thousand heads, while production reached 460. 91 thousand tons and then the numbers decreased in 2013 by%19, also decreased production by%31. 3, then the number rose in 2014 It has risen by%0. 22, and has maintained the same level of production and output in 2015. The study has reached a series of recommendations, including the importance of supporting and developing the production of red meat in Sudan through the adoption of economic policies encouraging investment and product stimulation, encouraging scientific research and introducing Animal in the agricultural cycle of government projects, the expansion of the use of improved breeds and the development of veterinary extension services and training leading to increase the production of red meat from goats in Sudan.
Keywords: livestock; goats; red meat; Sudan